Assessment of air and surfaces contamination in a COVID-19 non-Intensive Care Unit - Declementi, Michael; Godono, Alessandro; Mansour, Ihab; Milanesio, Nicolò; Garzaro, Giacomo; Clari, Marco; Fedele, Luca; Passini, Valter; Bongiorno, Carmela; Pira, Enrico (La Medicina del Lavoro, 2020)
Background: Severe Acute Respiratory Syndrome - Coronavirus – 2 (SARS-CoV-2) is a virus, primarily transmitted through droplets, able to persist on different surfaces and in the air for several hours. During the COVID-19 pandemic, Health Care Workers should be considered a high risk profession. Beside social distancing rules and the proper use of Personal Protective Equipment, sanitization measures and ventilation system disinfection are essential to reduce viral transmission. Objectives: This is the first Italian study aiming to assess the magnitude of environmental contamination in a COVID-19 non-Intensive Care Unit. Methods: In addition to ordinary cleaning procedures, surface and air samplings have been performed before and after the application of two different sanitization devices. Samples have been analyzed with Real Time-Polymerase Chain Reaction in order to find viral RNA. Results: All samples obtained from surfaces and air before and after extra-ordinary sanitization procedures turned out negative for viral detection. Discussion: These findings highlight the efficiency of ordinary cleaning procedures in guaranteeing a safer workplace. The adoption of additional sanitization protocols should be considered in order to further reduce environmental viral contamination.